Case report: Acute exacerbation of interstitial pneumonia related to messenger RNA COVID-19 vaccination. (March 2022) - Amiya, Saori; Fujimoto, Jun; Matsumoto, Kinnosuke; Yamamoto, Makoto; Yamamoto, Yuji; Yoneda, Midori; Kuge, Tomoki; Miyake, Kotaro; Shiroyama, Takayuki; Hirata, Haruhiko; Takeda, Yoshito; Kumanogoh, Atsushi
Highlights: Messenger RNA COVID-19 vaccine may cause acute exacerbation of interstitial pneumonia. Clinicians should recognize the risk and carefully monitor patients. Immunologic mechanism may be involved in the etiology of the exacerbation. Abstract: Messenger RNA (mRNA) vaccines that protect against COVID-19 are widely used in many countries owing to their high efficacy and safety profiles. Recently, few severe adverse events, such as anaphylaxis and myocarditis, were reported in healthy individuals. The safety of mRNA COVID-19 vaccines has not been adequately studied in patients with interstitial lung disease. We report 2 cases of acute exacerbation of preexisting interstitial pneumonia associated with mRNA COVID-19 vaccination. In both cases, lung disease was stable before the vaccination. Initial responses to steroid therapy were unfavorable, and intravenous cyclophosphamide was administered in both cases. Both patients were diagnosed with vaccine-related exacerbation of interstitial pneumonia based on laboratory results, radiologic features, and the observed clinical course, which lacked other causative events. We suggest that clinicians should note the possibility of acute exacerbation of pneumonia after mRNA COVID-19 vaccination and carefully monitor patients with interstitial lung disease.